1991
DOI: 10.3171/jns.1991.75.6.0856
|View full text |Cite
|
Sign up to set email alerts
|

Combined endovascular embolization and surgery in the management of cerebral arteriovenous malformations: experience with 101 cases

Abstract: The authors describe their experience with 101 cerebral arteriovenous malformations (AVM's) treated by endovascular embolization followed by surgical removal. Fifty-three patients presented with intracranial hemorrhage and 35 had seizures. Based on the classification of Spetzler and Martin, two AVM's were Grade I, 13 were Grade II, 26 were Grade III, 43 were Grade IV, and 17 were Grade V. Fifty-six AVM's were in the right hemisphere, 28 were in the left hemisphere, 12 were in the corpus callosum, and five invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
12

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(88 citation statements)
references
References 17 publications
2
74
0
12
Order By: Relevance
“…R. Dehdashti, et al come, have been documented in several series. 23,26 Staged embolization can reduce the risk of perfusion pressure breakthrough in patients with large AVMs and has enabled resection in some cases in which the lesion had been deemed previously untreatable. 6,23 Because of advanced techniques and devices, the rate of embolization-related complications has been dramatically reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. Dehdashti, et al come, have been documented in several series. 23,26 Staged embolization can reduce the risk of perfusion pressure breakthrough in patients with large AVMs and has enabled resection in some cases in which the lesion had been deemed previously untreatable. 6,23 Because of advanced techniques and devices, the rate of embolization-related complications has been dramatically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although not without complications, the endovascular procedure has proven to be an important adjuvant to the surgical treatment of intracranial AVMs. 1,7,8,19,26,27 Preoperative embolization should facilitate surgery by occluding the AVM nidus. Reduction of AVM volume and occlusion of aneurysms and high-flow fistulas are the desired effects of endovascular embolization.…”
mentioning
confidence: 99%
“…Según la literatura actual, la metodología a seguir en este tipo de tratamiento no queda bien establecida. Existe una gran variabilidad sobre el número de sesiones, el intervalo entre procedimientos y el porcentaje de embolización prequirúrgica en los artículos publica-394-405 dos 7,10,18,21,22,24,25,26,43,46,49 . Debido a ello, presentamos una revisión basada en nuestra experiencia y la literatura sobre los pasos a seguir a la hora de llevar a cabo el tratamiento combinado embolización más cirugía.…”
Section: Aspectos Del Tratamiento Combinado Embolización Más Cirugíaunclassified
“…Vinuela et al reported that out of 405 total patients, the AVM could only be cured in 9.9% of them, and those lesions that could be cured were relatively small in size [13,24]. Henkes et al have shown that endovascular embolization has succeeded in reducing the size of the nidus of AVM from 10-95% with complications only arising in 6% of 64 total patients [29].…”
Section: Presurgical Embolizationmentioning
confidence: 99%
“…Endovascular embolization prior to microsurgery is largely used when treating large AVM lesions [22][23][24][25][26]. Such a procedure has numerous advantages such as reduced blood loss, shorter surgical times, increased ability to occlude vessels difficult to control, and the benefit of staging flow reduction in the nidus [13,18].…”
Section: Presurgical Embolizationmentioning
confidence: 99%